Perception of the Discourse of Advertising Logos by Consumers of Mass Products: Case of Soft Drinks in Congo-Brazzaville (Global Journal of Management and Business Research, 2020)
Anchored in a perspective of relationship marketing, this article analyzes the perception of the discourse of advertising logos by consumers of soft drinks. Through a study carried out on 297 students, the article highlighted the fact that perception varies separately by level of education, gender, age, or a combination of both gender and level of education.
Keywords: relationship marketing; perception; logos; advertising; consumer; congo-brazzaville